Perception and attitude of nursing students toward e-learning - Jyotishman Mukhopadhyay; Sughandha Garg; Justin V Sebastian; Kiran Mini Ravi; Mallik, Debayan (Asian Journal of Medical Sciences, 2023)
Background: Information technology (IT) has undeniably eased out online teaching in days of social isolation. The sudden closure of institutions during the COVID-19 pandemic brought a halt in academics; later resumed through the inception of e-learning. Pandemics can neither be forecast nor overruled. Striding through this trying trend, it was thought prudent to determine nursing students’ attitude toward acceptance and practice of e-learning. Aims and Objectives: Striding through this trying trend, it was thought prudent to determine nursing students’ attitude toward acceptance and practice of e-learning. Materials and Methods: A descriptive cross-sectional study was conducted among 144 randomly selected nursing students of a Nursing College in Kolkata during August–October 2022. A self-administered structured questionnaire with demographic details incorporating a standard scale admeasuring attitude of students was used. Data were analyzed and validated statistically. Results: The majority used mobile set and cellular data as data-source (95 and 99%, respectively). Advantages of e-learning were screenshot of slides (96%), home-stay (94%), and reduced cost of hostel/transport (84%). Disadvantages included internet problems (83%) and inadequate bedside training (74%). Domain means for perceived usefulness, e-learning versus conventional learning, intention to adapt, ease of learning, and learning stresses were more than scale means reverberating higher acceptability. About 62.5% exhibited a favorable attitude toward e-learning. Family income, age, origin, and past experience were significantly associated with domains of e-learning; of which “Intent to get accustomed” was relevant. All domains related to e-learning found having significant positive correlation with each other indicating the strong value of e-learning among participants. Conclusion: As an alternative during the pandemic, 62.5% of prospective nurses showed a positive attitude toward e-learning. It is recommended that e-learning be made student-friendly through IT training making it a vital option for teaching-learning during catastrophic challenge.